2020
DOI: 10.1021/acsami.0c18590
|View full text |Cite
|
Sign up to set email alerts
|

Li2ZrO3-Coated NCM622 for Application in Inorganic Solid-State Batteries: Role of Surface Carbonates in the Cycling Performance

Abstract: All-inorganic solid-state batteries (SSBs) currently attract much attention as nextgeneration high-density energy storage technology. However, to make SSBs competitive with conventional Li-ion batteries, several obstacles and challenges must be overcome, many of which are related to interface stability issues. Protective coatings can be applied to the electrode materials to mitigate side reactions with the solid electrolyte, with lithium transition metal oxides, such as LiNbO3 or Li2ZrO3, being well establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 64 publications
3
82
0
Order By: Relevance
“…The discussed studies show that DEMS is a valuable tool to test and understand the stabilizing effect of CAM coatings in SSBs, recently also shown for Li 2 CO 3 /Li 2 ZrO 3 ‐coated NCM622. [ 73 ] This has been further demonstrated in the study of a system containing a poly(ethylene oxide) (PEO)‐based SE and LCO CAM. [ 74 ] As known from literature, such polymer SEs have a narrow electrochemical stability window.…”
Section: Characterization Techniquesmentioning
confidence: 96%
See 1 more Smart Citation
“…The discussed studies show that DEMS is a valuable tool to test and understand the stabilizing effect of CAM coatings in SSBs, recently also shown for Li 2 CO 3 /Li 2 ZrO 3 ‐coated NCM622. [ 73 ] This has been further demonstrated in the study of a system containing a poly(ethylene oxide) (PEO)‐based SE and LCO CAM. [ 74 ] As known from literature, such polymer SEs have a narrow electrochemical stability window.…”
Section: Characterization Techniquesmentioning
confidence: 96%
“…While the initial studies have been focused on the cathode side, such investigations need to be extended to the anode side (note that observations of H 2 evolution and CO 2 evolution at the very beginning of the initial charge cycle have been assigned to reactions possibly occurring at the anode). [ 67,71–73 ] Future studies aiming to create a more complete picture of interface/interphase formation in SSB cells could benefit from the combination of DEMS with X‐ray‐based techniques to reveal solid decomposition products along with gaseous species.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Previous literature reports revealed that this hybrid coating concept is also compatible with other materials than LiNbO 3 , for example, Li 2 ZrO 3 and Li 3 BO 3 , demonstrating the great versatility in terms of chemical composition (coating formulation) and properties [45][46][47]. In all of these cases, the coating was capable of suppressing to different extents interfacial decomposition of the solid electrolyte at the contact points with the CAM secondary particles, which otherwise would lead to impedance buildup due to formation of insulating degradation products (oxygenated sulfur and phosphorus species etc) and capacity fade.…”
mentioning
confidence: 88%
“…10,11 The degree of advancement of such decomposition reactions depends upon the quality of oxide coating but more so on the nature of the solid ionic conductor used. [12][13][14] Nowadays, a wide panel of fast Li + conductors for solid-state battery applications are known. The lithium thiophosphate family is probably the largest and one of the most attractive for practical applications.…”
Section: Introductionmentioning
confidence: 99%